Inhibition of Cardiac Kir Current (I(K1)) by Protein Kinase C Critically Depends on PKCβ and Kir2.2 - Scherer, Daniel (PLoS One, 2016)
BACKGROUND: Cardiac inwardly rectifying Kir current (I(K1)) mediates terminal repolarisation and is critical for the stabilization of the diastolic membrane potential. Its predominant molecular basis in mammalian ventricle is heterotetrameric assembly of Kir2.1 and Kir2.2 channel subunits. It has been shown that PKC inhibition of I(K1) promotes focal ventricular ectopy. However, the underlying molecular mechanism has not been fully elucidated to date. METHODS AND RESULTS: In the Xenopus oocyte expression system, we observed a pronounced PKC-induced inhibition of Kir2.2 but not Kir2.1 currents. The PKC regulation of Kir2.2 could be reproduced by an activator of conventional PKC isoforms and antagonized by pharmacological inhibition of PKCβ. In isolated ventricular cardiomyocytes (rat, mouse), pharmacological activation of conventional PKC isoforms induced a pronounced inhibition of I(K1). The PKC effect in rat ventricular cardiomyocytes was markedly attenuated following co-application of a small molecule inhibitor of PKCβ. Underlining the critical role of PKCβ, the PKC-induced inhibition of I(K1) was absent in homozygous PKCβ knockout-mice. After heterologous expression of Kir2.1-Kir2.2 concatemers in Xenopus oocytes, heteromeric Kir2.1/Kir2.2 currents were also inhibited following activation of PKC. CONCLUSION: We conclude that inhibition of cardiac I(K1) by PKC critically depends on the PKCβ isoform and Kir2.2 subunits. This regulation represents a potential novel target for the antiarrhythmic therapy of focal ventricular arrhythmias.